PERANAN PASAR MODAL DI INDONESIA - Neneng Yuhelmi (Jurnal Ilmiah Hukum dan Keadilan, 2016)
A phenomenon in life of company now days is that company is not satisfied itself moving in small scale otherwise in large scale. For that the mentioned company certainly needs capital. Hence, there are any alternative of taken choices by the company as effort or completion of the capital that is through capital market or through corporation of financial fond as source its view. If choice is capital market, thus the company will face investor in capital market. Investors in capital market is society, And society of companies will get addition of capital shell be used to develop company in more the larger scale.Based on reality mentioned above so there is question whether a set ofexisting rule can give law protection for investors in go public company through (capital market) securities exchange in Indonesia ?Principally all investors have similar objectives at the time invest is money in capital market that is profit. Because the same ob jective so they have high hope for openness from issuers concerning information and responsibility for real management of those company.To pay attention to possibility occurs impact of two interests or more in the capital market, so needs a set clear and accurate regulation, in other each the interest can be protective more fair. Event for investors, because those investor is generally society do not understand on many cases concerning capital market